Pemilihan Kepala Daerah dan Eksistensi Komunitas Masyarakat Adat Toraja - Tamma, Sukri (Jurnal Review Politik, 2017)
This paper showed how the Indigenous People in Indonesia reacts to the legal pluralism where they should respect their customary law while in same time must obey the formal laws. Based on research of the Toraja ethnic group in the Toraja Area in etno-metodology, the indigenous people was cleverly deal with the legal pluralism condition in regional election in 2015. Finally this paper shows how legal pluralism condition used by the Toraja ethnic group to keep their customary laws respected thru the regional election.